Analysis Relationship Between Internet Addiction and Self Efficacy with Cyberbullying Behavior in Adolescents: A Literature Review - Hanum Amalia Zulfa; Rizki Fitryasari; Lingga Curnia Dewi (Universitas Airlangga, 2020)
Introduction: Cyberbullying is an important issue because the perpetrator using the technology communication for threatened or endangered the others by intimidating their victims through technology devices and they repeatedly done it. The purpose of this research is to identify the connection between internet addiction and self efficacy with the behavior of cyberbullying on adolescents.Method: The research method used literature review design, literature review articles are searched in four electronic databases (Scopus, PubMed, Science Direct, Google Scholar. Variables that used to search the articles (cyberbullying, internet addiction, self efficacy). The Framework used to review is PICOS and the inclusion criteria used is English and Indonesian journals with issues from 2014 to 2020. The results of the article was found 10 studies which met inclusion criteria in the reviewe. Data tabulation and narrative analysis of study findings was performed.Results: The results showed that the adolescents who could not control their internet usage and use it for a long time as well as using it in impulsive way could make them involved in cyberbullying behavior where they could express their negative emotions and thoughts to others. Cyberbullying is also influenced by adolescents self-efficacy in solving cyberbullying problems by communicating online with the perpetrators using assertive language and being able to report cyberbullying events to reduce these actions.Conclusion: Adolescents with internet addiction is able to act in an unthinkable and uncontrolled way by expressing their negative emotions and thoughts by means of cyberbullying to others. adolescents who have the confidence in solving cyberbullying problems are make them able to prevent and report cyberbullying behaviour.